Evaluación en lenguas extranjeras: discursos y prácticas - Arias Toro, Clara Inés; Maturana Patarroyo, Liliana María (Íkala, Revista de Lenguaje y Cultura, 2005)
This article presents the results of a piece of research on foreign language teachers’ assessment discourse and practices carried out in two Colombian universities, with the aim of qualifying such practices. The main findings include: the confusing coexistence of summative and formative assessment; the imprecise definition of the linguistic construct in terms of skills; excessive emphasis on the organizational -not the pragmatic- area of language knowledge; the importance of non-linguistic aspects in pass/fail decisions; the indiscriminate use of assessment and testing, and the scarce consideration of several assessment task qualities. Additionally, the lack of teachers’ work stability, of clear assessment guidelines and agreement, and of formal and systematic recording of assessment results, contribute to teachers passing students without the required communicative competence. Received: 04-06-05/ Accepted: 26-07-05 How to reference this article: Arias Toro, C. I. & Maturana Patarroyo, L. M. (2005). Evaluación en lenguas extranjeras: discursos y prácticas. Íkala. 10 (1), pp. 63 – 91 <!–[endif]–>